VD_FINDINFO HC / 2015 / 261 vom 23. März 2015 - VD Tribunal cantonal (2015)
PROTECTION DE L'UNION CONJUGALE, ACTION EN MODIFICATION, MINIMUM VITAL, CONCUBINAGE | 163 CC, 176 CC, 179 CC, 271 CPC (CH), 296 CPC (CH)